Acta Conventus Neo-Latini Lovaniensis : Proceedings of the Eighteenth International Congress of Neo-Latin Studies (Leuven 2022) - Sacré, Dirk,; Schaffenrath, Florian, (Acta Conventus Neo-Latini ;, 2024)
Every third year, the members of the International Association for Neo-Latin Studies (IANLS) assemble for a week-long conference. Over the years, this event has evolved into the largest single conference in the field of Neo-Latin studies. The papers presented at these conferences offer, then, a general overview of the current status of Neo-Latin research; its current trends, popular topics, and methodologies. In 2022, the members of IANLS gathered for a conference in Leuven where 50 years ago the first of these congresses took place.This volume presents the conference's papers which were submitted after the event and which have undergone a peer-review process. The papers deal with a broad range of fields, including literature, history, philology, and religious studies.